ANALISIS PENGARUH SISTEM INFORMASI AKADEMIK TERHADAP KINERJA ORGANISASI PADA UNIVERSITAS ESA UNGGUL JAKARTA - Santosa, Lestanto Pudji (JIK: Jurnal Ilmu Komputer, 2016)
AbstractInformation system in built as a supporting facility for the development of information technology has increased and resulted in the rapid evolution of computer experience universities as educational organization have implemented information technology because of the increasing complexity of the problems faced one of the abstacies faced are academic and the student administration system. The system is expected to improve student academic administrative process although there are still shortcomings in practice. The study uses a model that Spurred on the update D&M IS success. The variable are in use in this study is the quality system, quality of information, quality of service and organization performance. The research method is the use explanatory, research in on location Esa Unggul University Jakarta. With the object of research with academic information system (SIAK) involving student and employees. Sample used 100 of the total population 3455, making the sample size formula Yamane, the instrument retrieval of data using questionnaires. The analysis used the descriptive statistical analysis and inferential statistical analysis linier multiple regression and correlation of determination. Hypothesis that are used in this study is the hypothesis that the first factor of the system quality, information quality and service quality simultaneously affect the performance of the organization and the second hypothesis is partially that the quality system significantly affect organizational performance, information quality affect the performance of the organization, and service quality significantly affect performance. Produce research results that all the proposed hypothesis is accepted.Keywords : The updated D&M IS Success models, multiple linier regression, determination